The role of the potato (Solanum tuberosum) CCD8 gene in stolon and tuber development. Issue 4 (15th March 2013) - Pasare, Stefania A.; Ducreux, Laurence J. M.; Morris, Wayne L.; Campbell, Raymond; Sharma, Sanjeev K.; Roumeliotis, Efstathios; Kohlen, Wouter; van der Krol, Sander; Bramley, Peter M.; Roberts, Alison G.; Fraser, Paul D.; Taylor, Mark A.
Summary: Strigolactones (SLs) are a class of phytohormones controlling shoot branching. In potato ( Solanum tuberosum ), tubers develop from underground stolons, diageotropic stems which originate from basal stem nodes. As the degree of stolon branching influences the number and size distribution of tubers, it was considered timely to investigate the effects of SL production on potato development and tuber life cycle. Transgenic potato plants were generated in which the CAROTENOID CLEAVAGE DIOXYGENASE8 ( CCD8 ) gene, key in the SL biosynthetic pathway, was silenced by RNA interference (RNAi). The resulting CCD8 ‐RNAi potato plants showed significantly more lateral and main branches than control plants, reduced stolon formation, together with a dwarfing phenotype and a lack of flowering in the most severely affected lines. New tubers were formed from sessile buds of the mother tubers. The apical buds of newly formed transgenic tubers grew out as shoots when exposed to light. In addition, we found that CCD8 transcript levels were rapidly downregulated in tuber buds by the application of sprout‐inducing treatments. These results suggest that SLs could have an effect, solely or in combination with other phytohormones, in the morphology of potato plants and also in controlling stolon development and maintaining tuber dormancy. Abstract : See also the Commentary by Mason